2015
DOI: 10.1016/j.dib.2015.10.041
|View full text |Cite
|
Sign up to set email alerts
|

Nemopilema nomurai Jellyfish venom treatment leads to alterations in rat cardiomyocytes proteome

Abstract: This data article restrains data associated to the Choudhary et al. [1]. Nemopilema nomurai Jellyfish venom (NnV) can lead to cardiac toxicity. Here we analyzed the effect of NnV on rat cardiomyocytes cell line H9c2 at the proteome level using two-dimensional gel electrophoresis and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF/MS). This analysis resulted in 34 proteins with differential expression. Here we provide the dataset for the proteins with amplified or reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Upon proper physical or chemical stimulation, such as human skin contact, nematocyst is rapidly discharged and everted thread penetrates into the skin and injects venom 6 . Jellyfish envenomation can be characterized by local effects (edema, burning sensation, erythematous eruption with small vesicle and necrosis) and sometimes the development of severe systemic reactions (cardiovascular alterations, hypovolemic shock, and respiratory collapse) 7 10 . Among these, cutaneous local tissue damage is most frequently observed in jellyfish stinging.…”
Section: Introductionmentioning
confidence: 99%
“…Upon proper physical or chemical stimulation, such as human skin contact, nematocyst is rapidly discharged and everted thread penetrates into the skin and injects venom 6 . Jellyfish envenomation can be characterized by local effects (edema, burning sensation, erythematous eruption with small vesicle and necrosis) and sometimes the development of severe systemic reactions (cardiovascular alterations, hypovolemic shock, and respiratory collapse) 7 10 . Among these, cutaneous local tissue damage is most frequently observed in jellyfish stinging.…”
Section: Introductionmentioning
confidence: 99%
“…On sudden stimulation, nematocysts explosively discharge various venom constituents into the preys or victims [4]. Many scientists performed toxicological research on NnV, which includes cardiotoxic, hepatotoxic, hemolytic and cytotoxic biological activities [5,6,7,8]. Edema, itching, burning sensation, and small vesicles with erythematous eruption appeared at the site of contact on the victim’s body after NnV envenomation [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…N. nomurai venom causes various symptoms that are mild or severe such as itching, redness, edema, hypotension, shock, and even death [ 9 ]. To date, several reports revealed that NnV induces cardiotoxic, cytotoxic, dermonecrotic, hemolytic, myotoxic, and proteolytic effects in in vitro and in vivo studies [ 10 13 ]. Our previous study has demonstrated that NnV has a proteolytic activity which is closely associated with cytotoxicity in skin cells [ 13 ].…”
Section: Introductionmentioning
confidence: 99%